Mad honey : a novel - Picoult, Jodi, 1966-; Boylan, Jennifer Finney, 1958- (New York : Ballantine Books, 2022)
Her life upended when her husband revealed a darker side, Olivia MacAfee and her teenage son Asher move back to her New Hampshire hometown for a new beginning until Asher is implicated in the death of his girlfriend and she realizes he$1 (Bs hidden more than he$1 (Bs shared with her.s
Maine author.
Keywords: Divorced women -- Fiction; Mothers and sons -- Fiction; Bee culture -- Fiction; Family violence -- Fiction; Trials (Murder) -- Fiction; Murder -- Investigation -- Fiction; New Hampshire -- Fiction; Domestic fiction